Do Bank Size And Age Moderate The Effect Of Credit Risk On Financial Sustainability In Indonesian Banks? - Fransiska Soejono; Carin Mareta; Eunike Stefani Mendrofa (Journal of Business and Management Inaba, 2026)
This study examines the effects of credit risk, bank size, and bank age on financial sustainability and evaluates the moderating roles of bank size and age in Indonesian banks. The sample comprises 168 bank-year observations from 29 banks during 2017–2024. Credit risk is proxied by the gross Non-Performing Loan ratio, whereas financial sustainability is measured using the Financial Sustainability Ratio. The baseline analysis employs pooled moderated regression with bootstrapping, while panel-data analysis accounts for unobserved bank-specific heterogeneity. The bootstrap results show significant positive coefficients for credit risk and bank size and a significant negative interaction between credit risk and bank size. Bank age and the credit risk–age interaction are insignificant. Panel-model selection identifies fixed effects as the appropriate specification. Under fixed effects with bank-clustered robust standard errors, credit risk, bank size, and both interactions are insignificant, while bank age has a positive and marginally significant direct effect at the 10% level. The contrast indicates that the significant pooled relationships mainly reflect differences across banks rather than consistent within-bank changes. The findings demonstrate that conclusions about credit risk and financial sustainability are sensitive to the treatment of bank-specific heterogeneity.